Mutation spectrum of 4-nitroquinoline N-oxide in the lacI transgenic Big Blue((R)) Rat2 cell line - Ryu, JC; Youn, JY; Kim, YJ; Kwon, OS; Song, YS; Kim, HT; Cho, KH; Chang, IM (ELSEVIER SCIENCE BV, 1999)
This paper describes the spectrum of mutations induced by 4-nitroquinoline N-oxide (4-NQO) in the lad target gene of the transgenic Big Blue(R) Rat2 cell line. There are only a few report for the mutational spectrum of 4-NQO in a mammalian system although its biological and genetic effects have been well studied. Big Blue(R) Rat2 cells were treated with 0.03125, 0.0625 or 0.125 mu g/ml of 4-NQO, the highest concentration giving 85% survival. Our results indicated that the mutant frequency (MF) induced by 4-NQO was dose-dependent with increases from three- to seven-fold. The DNA sequence analysis of lad mutants from the control and 4-NQO treatment groups revealed an obvious difference in the spectra of mutations. In spontaneous mutants, transition (60%) mutations, especially G:C --> A:T transition (45%), were most frequent. However, the major type of base substitution after treatment of 4-NQO was transversions (68.8%), especially G:C --> T:A (43.8%), while only 25% of mutants were transitions. These results are consistent with those produced by 4-NQO in other systems and the transgenic assay system will be a powerful tool to postulate more accurately the mechanism of chemical carcinogenesis involved. (C) 1999 Elsevier Science B.V, All rights reserved.